تأثير تدريبات المرونة بالمقاومات (Ki-Hara) بمصاحبة أسطوانة الفوم (Foam Roller) على بعض المتغيرات البدنية والمستوى الرقمي لمسابقة عدو 100 م. حواجز - نور الدين، نجلاء البدري Nouruldin, Najla Albadri (جامعة سوهاج - كلية التربية الرياضية, 2018)
يهدف البحث إلى التعرف على تأثير تدريبات المرونة بالمقاومات (Ki-Hara) بمصاحبة أسطوانة الفوم (Foam Roller) على بعض المتغيرات البدنية والمستوى الرقمي لمسابقة 100 م حواجز. واستخدمت الباحثة المنهج التجريبي بتصميم تجريبي لمجموعه تجريبية واحدة يعتمد على المقارنة بين القياسين القبلي والبعدي. وتم تطبيق البحث على عينة بلغت (10) لاعبات من منتخب جامعة حلوان بالإضافة إلى طالبات كلية التربية الرياضية بنات جامعة حلوان واللاتي لهن أرقام تتقارب مع المستوي الرقمي للاعبات منتخب جامعة حلوان، وقد أسفرت اهم نتائج البحث إلى وجود فروق ذات دلالة إحصائية بين القياسين القبلي والبعدي للمجموعة التجريبية في مرونة الكتف ثني، مرونة الكتف مد، مرونة العمود الفقري ثني، مرونة العمود الفقري مد، مرونة ركبه ثنى، مرونة قدم ثنى، مرونة قدم مد، زمن التسارع (10 م)، زمن رد الفعل لصالح القياس البعدي.
The research aims to identify the impact of flexibility training with resistances (Ki-Hara) with the foam cylinder (Foam Roller) on some physical variables and the digital level of the 100-meter hurdles competition. The researcher used the experimental method with ah experimental design for one experimental group based on a comparison between the pre and post measurements. The research was applied to a sample of (10) female players from the Helwan University team in addition to the students of the Faculty of Physical Education for the girls of Helwan University who have numbers converging with the digital level of the players of the Helwan University team, and the most important results of the research resulted in the presence of statistically significant differences between the pre and post measurements For the experimental group in shoulder elasticity drape, shoulder d stretch flexibility, spine flexion elasticity, spine elasticity d stretch, knee flexion elasticity, flexion foot elasticity, tread foot elasticity, acceleration time (10 m), reaction time in favor of dimensional measurement.
Keywords: التربية الرياضية -- التدريبات الرياضية -- المتغيرات البدنية -- ألعاب القوى -- الجري والعدو